A jammer's perspective of reachability and LQ optimal control. (August 2016) - Sukumar, Srikant; Chatterjee, Debasish
Abstract: This article treats two problems dealing with control of linear systems in the presence of a jammer that can sporadically turn off the control signal. The first problem treats the standard reachability problem, and the second treats the standard linear quadratic regulator problem under the above class of jamming signals. We provide necessary and sufficient conditions for optimality based on a nonsmooth Pontryagin maximum principle.